2021
DOI: 10.3332/ecancer.2021.1248
|View full text |Cite
|
Sign up to set email alerts
|

Determining the prevalence of high-risk human papillomavirus infection using a novel cervical precancer screening approach in incarcerated women at the Nsawam Medium Security Prison, Ghana

Abstract: Background: Across Ghana, females comprise 1.2% of the entire prison population (n = 15,463). Cervical cancer screening services are however nonexistent and the prevalence of high-risk human papillomavirus (hr-HPV) and cervical precancer is undocumented. We aimed to screen and treat inmates for cervical precancer and determine the prevalence of hr-HPV using the novel AmpFire HPV detection system combined with colposcopy by trained nurses using a mobile colposcope (the Enhanced Visual Assessment (EVA) system).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 23 publications
1
15
0
3
Order By: Relevance
“…It is reported that the squamocolumnar junction recedes into the endocervical canal and is not visible for majority of women after 45 years (TZ type 3). This is in line with the high proportion of transformation type 3 seen in our study [19]. Again cytology histology correlation must be adopted by all reporting laboratories to ensure and guarantee CQI.…”
Section: Discussionsupporting
confidence: 80%
“…It is reported that the squamocolumnar junction recedes into the endocervical canal and is not visible for majority of women after 45 years (TZ type 3). This is in line with the high proportion of transformation type 3 seen in our study [19]. Again cytology histology correlation must be adopted by all reporting laboratories to ensure and guarantee CQI.…”
Section: Discussionsupporting
confidence: 80%
“…Our staff at the CCPTC have worked hard training all cadres of health workers. They have screened women in all corners in the country including screening head porters (kayayei), commercial sex workers, nuns and prisoners [ 19 ]. Our alumni across the country are also screening women in communities that would otherwise not have seen this for many years.…”
mentioning
confidence: 99%
“…Супутні інфекції, що передаються статевим шляхом, з урахуванням УПМ та ВІЛ, значно збільшують вірогідність зараження ВПЛ через статевий контакт [5,6,8,10,17,19,21]. На сьогодні окрему увагу серед ІПСШ заслуговує урогенітальна трихомонадна інфекція, як найбільш поширена у світі та в більшості випадках (до 70%) представляє собою змішаний процес з іншими ІПСШ.…”
Section: вступunclassified
“…Це обумовлює можливість тривалої персистенції бактерій, грибів і вірусів, зокрема, ВПЛ всередині трихомонад і дозволяє пояснити невдалі спроби діагностики та елімінації відповідних мікроорганізмів [3,17,19]. Також за даними літератури змішана інфекція, що передається статевим шляхом, та ВПЛ збільшує в рази ризик РШМ [5,10,17,20].…”
Section: вступunclassified